2013
DOI: 10.1590/0037-8682-0168-2013
|View full text |Cite
|
Sign up to set email alerts
|

Blood feeding patterns of Nyssomyia intermedia and Nyssomyia neivai (Diptera, Psychodidae) in a cutaneous leishmaniasis endemic area of the Ribeira Valley, State of São Paulo, Brazil

Abstract: Introduction:The aim of this study was to identify the blood feeding sources of Nyssomyia intermedia (Ny. intermedia) and Nyssomyia neivai (Ny. neivai), which are Leishmania vectors and the predominant sandfl y species in the Ribeira Valley, State of São Paulo, Brazil, an endemic area for cutaneous leishmaniasis. Methods: Specimens were captured monthly between February 2001 and December 2003 on a smallholding and a small farm situated in the Serra district in the Iporanga municipality. The blood meals of 988 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In other words, the presence of animal species different from rats was a protection factor against leishmaniosis in rats (OR= 0.01273 to 0.8341). A study on Nyssomyia neivai species broadly found in Paraná State (MEMBRIVE et al, 2004;DIAS-SVERSUTTI et al, 2007;SILVA et al, 2008;CERINO et al, 2009;CRUZ et al, 2013;MELO et al, 2013), performed in Ribeira Valley São Paulo State, examined 988 engorged females, and no rat blood was detected in the phlebotomines (MARASSÁ et al, 2013). According to Dias-Sversutti et al (2007), N. neivai and N. whitmani are opportunists and probably adjust their feeding habits based on the availability of hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the presence of animal species different from rats was a protection factor against leishmaniosis in rats (OR= 0.01273 to 0.8341). A study on Nyssomyia neivai species broadly found in Paraná State (MEMBRIVE et al, 2004;DIAS-SVERSUTTI et al, 2007;SILVA et al, 2008;CERINO et al, 2009;CRUZ et al, 2013;MELO et al, 2013), performed in Ribeira Valley São Paulo State, examined 988 engorged females, and no rat blood was detected in the phlebotomines (MARASSÁ et al, 2013). According to Dias-Sversutti et al (2007), N. neivai and N. whitmani are opportunists and probably adjust their feeding habits based on the availability of hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigations of the blood meals of various species of sand flies are crucial towards a better assessment of the risk of Leishmania transmission in areas where leishmaniasis are endemic. Several methodologies to identify blood meal in sand flies have been used, including enzyme-linked immunosorbent assay (ELISA), mass spectrometry, precipitin test and polymerase chain reaction (PCR) [6][7][8][9][10][11]. More recently, quantitative real-time PCR [12,13] and PCR followed by amplicon sequencing [14] demonstrated promising results, with high-level sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been traditionally applied to study the blood-feeding behaviour of sand flies, including the precipitin test [ 4 , 7 , 11 - 13 ] and ELISA [ 14 - 16 ]. However, these methods present some technical limitations (e.g., the possibility of cross-reactivity between species, the need for producing specific antibodies to several species, and the inability to discover unpredicted hosts) ([ 10 ]; and references cited therein).…”
Section: Introductionmentioning
confidence: 99%